Quality Matters: A Global Discussion in Qatar - Salman, Ayat (Biopreserv Biobank, 2019)
The International Biobanking Conference titled “Quality Matters: A Global Discussion in Qatar” was held on March 25–27, 2019, in the vibrant city of Doha, Qatar. The 3-day event was organized and hosted by the Qatar Biobank (QBB) and the European, Middle Eastern and African Society for Biopreservation and Biobanking (ESBB), with supporting collaboration from the International Society for Biological and Environmental Repositories (ISBER) and the Biobanking and BioMolecular Resources Research Infrastructure—European Research Infrastructure Consortium (BBMRI-ERIC). The aim was to highlight the role of biobanking in medical research and advancing health care, as well as improving clinical outcomes. The conference convened experts from across the globe to discuss continuing efforts to harmonize biobanking-related processes to achieve high-quality standards and to support international advancements in medical research for our diverse populations. The scientific agenda drew more than 1000 scientists, researchers, industry experts, and health professionals from five continents. The conference focused on the quality aspect of biobanking through seven sessions over 3 days. Researchers, scientists, and experts from around the world were invited to present, and included special presentations from QBB demonstrating their standing as a leading clinical biobank innovator in support of population and genomic medicine. The 3-day conference concluded with a session on Best Practices and Standards, a topic much in discussion with today's context.